New Approaches to Organizational CommunicationNew Approaches to Organizational Communication, edited by KovacicBranislav. Albany: State University of New York Press. - Mumby, Dennis (Academy of Management Review, 1996)
The article reviews the book ?New Approaches to Organizational Communication,? edited by Brasnilav Kovacic.